Numerical analyses of piezoceramic actuators for high temperature applications. (1st September 2016) - Zappino, E.; Carrera, E.; Rowe, S.; Mangeot, C.; Marques, H.
Abstract: The present work, performed in the frameworks of the CleanSKY project AeroPZT, is devoted to the numerical analysis of innovative actuators made of piezoelectric materials. An advanced numerical tool, based on the Carrera Unified Formulation, have been used to perform numerical analyses of the device. A refined one-dimensional structural model has been used in the analyses to provide accurate results with a low computational cost. Thermal loads and the effects of the encapsulation, which is used to protect the piezoelectric element from the external environment, have been evaluated. Amplified Piezoelectric Actuators (APAs) and a Multi-Layered Actuators (MLAs) have been analysed. The obtained results have been used to derive guidelines for the development of the final design of the actuator able to satisfy the project requirements.